Knowledge, attitude, and practice regarding the risk of cardiovascular diseases in patients attending outpatient clinic in Kuantan, Malaysia - Nursyafiza B Mohammad; Nor Azlina A Rahman; Mainul Haque (Wolters Kluwer Medknow Publications, 2018)
Background: Cardiovascular disease (CVD) is a leading cause of death around the world including Malaysia. Ischemic heart disease (IHD) is the single largest cause of death in the developed countries and is one of the main contributors to the disease burden in developing countries. Materials and Methods: This was a cross-sectional study conducted to determine knowledge, attitude, and practice (KAP) regarding the risk of CVD in patients attending an outpatient clinic in Kuantan, Malaysia. A total of 100 patients comprising 52 male and 48 female subjects were selected through convenient sampling method. Results: Of the total subjects, 86% were Malays. The mean scores (standard deviation) for KAP were 60.75±4.823, 54.36±8.711, and 33.43±4.046, respectively, whereas the maximum scores obtained by the subjects for KAP were 71, 65, and 43, respectively. Regarding questions related to knowledge, 88% subjects knew irregular eating pattern can cause disease and the benefits of vegetable intake. Most subjects recognized that smoking and obesity were CVD risk factors. Regarding questions related to attitude, 96% agreed that exercise can prevent CVD. More than half of the subjects followed healthy lifestyle. There were statistically significant differences observed in knowledge level between sexes (P = 0.046) and races (P = 0.001). Nevertheless, there was no statistically significant difference observed in KAP across different education levels of the subjects regarding the risk of CVD (P-value = 0.332, 0.185, and 0.160, respectively). Conclusion: This study revealed that patients had good knowledge and attitude regarding CVD risk factors. Yet, the number of smokers is still quite high. Development of better public information system is essential for the well-being of the society.